PENINGKATAN HASIL BELAJAR SISWA KELAS V SD PADA TEMA SIKLUS AIR MELALUI STRATEGI PBL BERBASIS TPACK DENGAN BANTUAN DIORAMA SIKLUS AIR SEBAGAI BENDA KONKRET - sudrajat; Anita Sari; Nindy Mardiani (Universitas Muhammadiyah Metro, 2025)
This Classroom Action Research (CAR) was conducted with the aim of improving the science learning outcomes of fifth-grade elementary school students, particularly in understanding the concept of the water cycle. The study employed the Problem Based Learning (PBL) strategy, integrated with the Technological Pedagogical Content Knowledge (TPACK) framework, to enhance both the pedagogical process and student engagement. The integration of concrete media in the form of dioramas and digital support through an interactive water cycle simulation application was used to help students visualize abstract scientific processes and build a deeper conceptual understanding. The research was carried out in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. Data were collected through tests (pretest and posttests), observations, and student learning activity documentation. The findings revealed a significant increase in students’ academic performance. The average score improved from 61,2 in the pretest to 72,3 in the first cycle, and further increased to 92.6 in the second cycle. The percentage of students achieving the minimum mastery criteria (≥75) rose from 17% in the pretest to 47% in cycle I, and finally to 91% in cycle II. This demonstrated that students not only acquired better cognitive understanding but also showed greater involvement, problem-solving skills, and collaborative attitudes throughout the learning process. The study concludes that the application of the PBL strategy combined with the TPACK framework and supported by relevant media significantly contributes to improving science learning outcomes in elementary education. Furthermore, it provides a meaningful learning experience that encourages critical thinking, inquiry, and the use of digital tools to construct scientific knowledge. These findings suggest that this model of instruction can serve as a reference for future practices and further research in science education, particularly for complex and abstract topics.